2022
DOI: 10.3389/fmicb.2022.955913
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial and fungal communities in indoor aerosols from two Kuwaiti hospitals

Abstract: The airborne transmission of COVID-19 has drawn immense attention to bioaerosols. The topic is highly relevant in the indoor hospital environment where vulnerable patients are treated and healthcare workers are exposed to various pathogenic and non-pathogenic microbes. Knowledge of the microbial communities in such settings will enable precautionary measures to prevent any hospital-mediated outbreak and better assess occupational exposure of the healthcare workers. This study presents a baseline of the bacteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 88 publications
0
32
0
Order By: Relevance
“…Nucleic acid quantification was performed on a Qubit fluorometer employing the Qubit HS DNA/RNA assay kits (Thermo Scientific, Waltham, MA, USA). All the RNA samples (HI-1 and HI-2), were converted to complementary DNA (cDNA) before conducting the PCR [ 20 , 21 ]. K-O and K-I samples collected in a month ( n = 4; one sample per week) were pooled due to their low biological yields.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleic acid quantification was performed on a Qubit fluorometer employing the Qubit HS DNA/RNA assay kits (Thermo Scientific, Waltham, MA, USA). All the RNA samples (HI-1 and HI-2), were converted to complementary DNA (cDNA) before conducting the PCR [ 20 , 21 ]. K-O and K-I samples collected in a month ( n = 4; one sample per week) were pooled due to their low biological yields.…”
Section: Methodsmentioning
confidence: 99%
“…Air as a medium for ARG dissemination is less explored [ 16 ]. Aerosols are known carriers of many pathogenic microbes [ 17 , 18 , 19 , 20 , 21 ]; it is, therefore, legitimate to speculate that they can be transmitters of ARGs. A study in China has reported the rate of ARG inhalation ranging from 10 3 to 10 4 copies per day by an adult [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In total, 16 articles were subjected to a full-text analysis, from which 3 were excluded due to not meeting the inclusion criteria (measurements of the exhaled air or non-English papers). In total, 13 articles were qualified for analysis in this systematic review [3,26,[34][35][36][37][38][39][40][41][42][43][44].…”
Section: Study Selectionmentioning
confidence: 99%
“…Most of the studies examined the aerosols present in different hospital areas such as wards, operating rooms, nursing stations, waiting rooms, textile rooms, corridors, etc. [3,26,[34][35][36][37][38][39][40][41][42][43]. Among all included studies, one focused on aerosols produced during dental prophylaxis with an ultrasonic scaler [44].…”
Section: General Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Workers in the healthcare sector are exposed to microbial contaminants via several routes [1]. Indoor air circulating within hospitals, laboratories, and ancillary areas contains a variety of microbial communities and is considered the most viable channel to transmit them to human occupants via inhalation [2][3][4][5]. The anterior nasal cavity is the primary point of entry of these bacteria into the respiratory system of humans [6].…”
Section: Introductionmentioning
confidence: 99%